Assimilate enhancement on the carbohydrates and nitrogen content in maize - Magalhães, Paulo César; Jones, Robert (Pesquisa Agropecuaria Brasileira, 2014)
Studies showed that maize (Zea mays L.) grain yield and quality is limited by the availability of assimilates during grain filling. The objective of this work was to study the effects of assimilate enhancement on the soluble sugars and nitrogen content in the internodes and grain. Two genotypes were used: M14 x W64A and Pioneer 3780. The treatments consisted of partial kernel removal and thinning by 50% plant population reduction imposed 6 and 24 days after silking. M14 x W64A responded positively to thinning and partial kernel removal in both dates, by increasing soluble sugar content in the internodes. The early kernel removal increased the internode N content, whereas early thinning resulted in greater grain starch content. Pioneer 3780 showed nitrogen content in the internodes and grains and internode soluble sugar content increased by the treatments imposed either at 6 or 24 days alter silking. The greater soluble sugar content in the internodes not always was translocated and accumulated in the grain. Invertase efficiency and sink capacity may be envolved in these processes.